2011
DOI: 10.1016/j.jss.2011.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Indocyanine Green Retention Rate at 15 Minutes by Correlated Liver Function Parameters before Hepatectomy

Abstract: Background. Indocyanine green retention rate at 15 minutes (ICGR15) is a useful marker

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The exact interaction between ICG and bilirubin transport carriers has yet to be elucidated . As a result, a low measured ICG elimination should be interpreted with caution in patients with obstructive jaundice .…”
Section: Liver Function Monitoring Using Icgmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact interaction between ICG and bilirubin transport carriers has yet to be elucidated . As a result, a low measured ICG elimination should be interpreted with caution in patients with obstructive jaundice .…”
Section: Liver Function Monitoring Using Icgmentioning
confidence: 99%
“…Finally, in patients with biliary obstruction, a decreased ICGR15 value may be found, possibly falsely suggesting impaired liver function . In these patients, the pre‐operative ICGR15 value should be interpreted with caution, and should not be used to justify withholding intended curative surgery.…”
Section: Peri‐operative Point‐of‐care Monitoring Using Icg Kinetics Amentioning
confidence: 99%
“…It is important to evaluate hepatic reserve prior to hepatic resection, and the permissible extent of resection is considered on the basis of presence or absence of ascites, jaundice and the indocyanine green (ICG) retention rate at 15 min when determining the type of resection procedure 5 . If necessary, technetium‐99 m diethylenetriamine pentaacetic acid galactosyl human serum albumin single photon emission computed tomography (CT) is used to evaluate patients who cannot be adequately evaluated by means of an ICG load test 6,7 …”
Section: Hepatic Resectionmentioning
confidence: 99%
“…5 If necessary, technetium-99m diethylenetriamine pentaacetic acid galactosyl human serum albumin single photon emission computed tomography (CT) is used to evaluate patients who cannot be adequately evaluated by means of an ICG load test. 6,7 According to the report of the 18th follow-up survey of primary liver cancer in Japan, hepatic resection was performed in 31.7% of all cases of HCC, with operative mortality of 1.4% (Fig. 2).…”
Section: Hepatic Resectionmentioning
confidence: 99%
“…In previous studies, indocyanine green, which was the main material for ICG-hyaluronic acid mixture, was already used for medical purposes. For example, the indocyanine green retention rate at 15 min (ICGR15) is a useful marker of liver function in deciding on the extent of hepatectomy (13). In addition, Mok et al reported that Indocyanine green encapsulated hyaluronic acid nanogels were used for highly selective detection of speci c cancers and lymph nodes (14).…”
Section: Discussionmentioning
confidence: 99%